HYBRIDIZED SPIRITUAL–TOTAL QUALITY MANAGEMENT IN ISLAMIC BOARDING SCHOOLS: MANAGING A SUSTAINABLE ARABIC LANGUAGE ENVIRONMENT - Zainal Abidin; Akhmad Fauzi Hamzah; Ahmad Qusairi; Musleh Harry; Ikmal Wahyudi (STAI Ma'had Aly Al-Hikam Malang, 2026)
This study aims to look into the management of the Arabic language environment (Biah Arabiyah) in Pondok Pesantren Darullughah Wadda’wah (Dalwa), Indonesia, using the Total Quality Management (TQM) theory with the integration of spiritual values. This study sought to explore the role of the management of the organization in the sustainability of the Arabic Language Environment. This current study used a qualitative case study method. Participants of the current study included the pesantren management, the language program management, teachers, and students, as they were the key individuals involved in the implementation of the Arabic Language Environment. Thematic analysis of the data revealed the following findings: The sustainability of the Arabic Language Environment is supported by the following three mechanisms: the planning of the language environment, the embedding of the use of the Arabic Language in the academic and social activities of the pesantren, and the supervision of the institution. In addition, spiritual values embedded in the pesantren culture strengthen students’ intrinsic motivation to maintain the use of Arabic in daily communication. These findings lead to the development of a conceptual framework called the Hybridized Spiritual–TQM Model, which integrates quality management principles with spiritual values to sustain the language learning environment. Keywords: Arabic Language Environment; Spiritual Culture; Total Quality Management. Abstrak Penelitian ini bertujuan untuk mengkaji pengelolaan lingkungan berbahasa Arab (Biah Arabiyah) di Pondok Pesantren Darullughah Wadda’wah (Dalwa), Indonesia, menggunakan teori Total Quality Management (TQM) dengan integrasi nilai-nilai spiritual. Penelitian ini berupaya mengeksplorasi peran manajemen organisasi dalam keberlanjutan Lingkungan Berbahasa Arab. Penelitian ini menggunakan pendekatan kualitatif jenis studi kasus. Partisipan meliputi manajemen pesantren, manajemen program bahasa, guru, dan siswa, karena mereka adalah individu kunci yang terlibat dalam implementasi Lingkungan Berbahasa Arab. Analisis tematik data mengungkapkan temuan sebagai berikut: Keberlanjutan Lingkungan Berbahasa Arab didukung oleh tiga mekanisme berikut: perencanaan lingkungan bahasa, pengintegrasian penggunaan Bahasa Arab dalam kegiatan akademik dan sosial pesantren, dan pengawasan lembaga. Selain itu, nilai-nilai spiritual yang tertanam dalam budaya pesantren memperkuat motivasi intrinsik siswa untuk mempertahankan penggunaan Bahasa Arab dalam komunikasi sehari-hari. Temuan-temuan ini mengarah pada pengembangan kerangka kerja konseptual yang disebut Model Spiritual-TQM Hibrida, yang mengintegrasikan prinsip-prinsip manajemen mutu dengan nilai-nilai spiritual untuk mempertahankan lingkungan pembelajaran bahasa. Kata kunci: Budaya Spiritual; Lingkungan Bahasa Arab; Manajemen Mutu Total.